Energy education: breaking up the rational energy use barriers - Dias, R. A.; Mattos, C. R.; Balestieri, José Antônio Perrella [UNESP] (Elsevier B.V., 2004)
Human development is associated directly or indirectly with the energy use, and because of this the energetic sources were dealt with in the recent past, as fully available to human necessities. The reality shows that the energy availability, considering the nonrenewable sources, is limited, and beyond that, the exploration, the processing and the use of energy impose considerable impacts on the environment. There is not a system which operates with no losses and without imposing changes to the environment. Therefore, the energy conservation incorporates the concepts and the actions applied to the research of sustainable balance between nature and the energy availability and use. Such actions can be presented both in the short term, in which the energy system is close to a collapse, or in the medium/long term, in which those responsible for the energy policies are concerned with the structure of the socioeconomic development. Such a situation requires more responsibility in the treatment of energy questions, mainly through education, which represents long-term investments. This paper discusses barriers that are present in the projects applied to energy conservation, by making clear that education is one of the best ways to transform the human behavior in for the rational use of energy. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: energy conservation; science education; energy policy